Meningkatkan Kedisiplinan Anak Usia Dini Melalui Latihan Pembiasaan Penggunaan Toilet di KB Al-Hidayah Insan Mandiri Kabupaten Bandung - Dikdik Pramono; Anni Risnawati (LPPM Universitas Pahlawan Tuanku Tambusai, 2018)
The purpose of this research is to know the discipline of early childhood through the habitual use of toilet training well in KB Al-Hidayah Insan Mandiri Kabupaten Bandung. Good toileting habits can help early childhood knowledge and understanding about how to use the toilet properly, maintain hygiene, and help lay out aspects related to using toilets to improve child self-discipline. The research problem is how to improve the discipline of early childhood through the use of toilet in KB Al-Hidayah Insan Mandiri Kabupaten Bandung. The research method used is classroom action research method. The classroom action research in this study consisted of two cycles, each cycle of three meetings conducted in the even semester (academic year 2017-2018), then the data were analyzed quantitatively and qualitatively. The subjects of this study are early childhood KB Al-Hidayah Insan Mandiri Kabupaten Bandung, amounting to 20 children. The instrument used in this study is a child observation sheet. The results showed that through the use of toilets well can improve the early childhood discipline in KB Al-Hidayah Insan Mandiri Kabupaten Bandung by 85%.